Ela mulher, ele vários: marcas de gênero nas notícias do portal G1 - Santos, Suely Porfirio dos (2019)
Taking into account the importance of journalism to the social construction of reality, this paper analyzed how gender relations are materialized in the journalistic contents published on G1, the most visited site in Brazil according to the web traffic data collected by the Alexa website. Based on the concept of gender as a means of social identity construction of men and women (SAFFIOTI, 2015; SCOTT, 1996), as well as the proposal of dimensions of gender inequalities (BIROLI, 2018), this paper seeks to understand how the news acts as a means of construction of genders. This paper analyzed 437 stories published on G1 between April and May of 2019. The research was conducted in two phases. The first phase was based on the Pragmatic Analysis of the Journalistic Narrative (MOTTA, 2008) as a method to provide the meaning present in each story. The second phase was based on Discourse Analysis so that the relation between the meanings found in the news and the assignments to people by gender was made. The Discourse Analysis reveals that what is said by a subject reproduces the ideas present in a certain historical period, place, and social condition (ORLANDI, 1997). For this reason, we could realize the social reality constructed (BERGUER; LUCKMAN, 2011) by G1 was marked by a differentiated and unequal treatment of people. The data shown men were the main characters in seven of ten stories published and they featured as subject referential and were prominent even in the narratives where they are not central. As for the women, they were depicted in the roles of mother and wife, also they were highlighted by their aesthetic features and their images were explored in about half of the content. When the stories depicted women in a political and legal environment, which were the case in a small part of the stories, the treatment follows the same pattern as the stories where the men had central roles.